Quantitative comparisons between optical coherence tomography angiography and matched histology in the human eye. (May 2018) - An, Dong; Balaratnasingam, Chandrakumar; Heisler, Morgan; Francke, Ashley; Ju, MyeongJin; McAllister, Ian L.; Sarunic, Marinko; Yu, Dao-Yi
Abstract: The aim was to quantitatively compare retinal vascular detail as seen on optical coherence tomography angiography (OCTA) and matched histology in the human eye. 13 normal human donor eyes were used. The central retinal artery was cannulated after which human packed red blood cells were perfused through the retinal vasculature. Retinal vessels were imaged using a custom-built OCTA device during red blood cell perfusion. The eye was subsequently perfused with endothelial cell antibodies and the flat-mounted retina studied histologically using a confocal scanning laser microscope. Qualitative and quantitative comparisons of retinal vascular information as seen on OCTA and histology from the same region of interest were performed. Gradable OCTA images were acquired from 4 of 13 eyes with mean postmortem-to-OCTA imaging time of 4.5 ± 1.3 h 23 pairs of OCTA-histology matched images were evaluated. The retinal arteries and veins had similar pixel intensity on OCTA images. The diameter of retinal veins was significantly greater than its paired artery on OCTA (P < 0.001). The density of vascular structures on OCTA (40.2% ± 10.1%) was significantly less than matched histology (52.1% ± 9.3%, P < 0.001). Mean capillary diameter on OCTA (10.2 ± 2.4 μm) was significantly greater than histology (8.2 ± 2.4 μm; P < 0.001). This is the first study to directly compare OCTA against histology from the same human eye. OCTA visualizes many of the vascular structures in the human retinal circulation but does not exactly match what is seen on histologic examination. Highlights: Density of retinal vessels was significantly greater on micro-perfusion labeled histology compared to OCTA. Vessel density is greater on histology than OCTA for which intervening vascular beds between large vessels were sometimes not visualized. Arteries and veins could not be distinguished on OCTA using pixel intensity. Veins generally had larger diameter than their paired arteries.